Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\frac{3}{5}\times y+\frac{1}{2}:\frac{5}{3}-\frac{5}{4}=\frac{1}{2}\times\frac{1}{3}\)
\(\Rightarrow\frac{3}{5}\times y+\frac{3}{10}-\frac{5}{4}=\frac{1}{6}\)
\(\Rightarrow\frac{3}{5}\times y+\left(-\frac{19}{20}\right)=\frac{1}{6}\)
\(\Rightarrow\frac{3}{5}\times y=\frac{67}{60}\)
\(\Rightarrow y=\frac{67}{36}\)
b) \(\frac{4}{5}:y+\frac{1}{4}\times\frac{1}{6}-\frac{1}{2}=\frac{1}{3}\times\frac{5}{2}\)
\(\Rightarrow\frac{4}{5}:y+\frac{1}{24}-\frac{1}{2}=\frac{5}{6}\)
\(\Rightarrow\frac{4}{5}:y+\left(-\frac{11}{24}\right)=\frac{5}{6}\)
\(\Rightarrow\frac{4}{5}:y=\frac{5}{6}+\frac{11}{24}=\frac{31}{24}\)
\(\Rightarrow y=\frac{4}{5}:\frac{31}{24}=\frac{96}{155}\)
c) \(\frac{3}{5}\times y-\frac{4}{5}:3+\frac{1}{12}=\frac{3}{2}+\frac{1}{5}\)
\(\Rightarrow\frac{3}{5}\times y-\frac{4}{15}+\frac{1}{12}=\frac{17}{10}\)
\(\Rightarrow\frac{3}{5}\times y-\frac{4}{15}=\frac{97}{60}\)
\(\Rightarrow\frac{3}{5}\times y=\frac{113}{60}\)
\(\Rightarrow y=\frac{113}{36}\)
a) \(\frac{27}{36}=\frac{3}{4}\)
b) \(\frac{45}{60}=\frac{3}{4}\)
c) \(\frac{2}{4}=\frac{1}{2}\)
d) \(\frac{10}{12}=\frac{5}{6}\)
e) \(\frac{112}{252}=\frac{4}{9}\)
Đúng nha bạn !!@@
\(\frac{1}{3}+\frac{3}{4}x\frac{5}{9}=\frac{1}{3}+\frac{5}{12}=\frac{3}{4}\)
\(\frac{7}{12}-\frac{5}{4}x\frac{2}{15}=\frac{7}{12}-\frac{1}{6}=\frac{5}{12}\)
\(y+\frac{1}{4}=\frac{7}{8}-\frac{3}{8}=y+\frac{1}{4}=\frac{1}{2}=\frac{1}{2}-\frac{1}{4}=\frac{1}{4}\)
\(y-\frac{5}{12}=\frac{2}{3}-\frac{1}{4}=y-\frac{5}{12}=\frac{5}{12}=\frac{5}{12}+\frac{5}{12}=\frac{5}{6}\)
\(\frac{12}{7}xy=\frac{16}{21}=\frac{16}{21}:\frac{12}{7}=\frac{4}{9}\)
\(\frac{5}{4}:y=\frac{7}{12}=\frac{5}{4}:\frac{7}{12}=\frac{15}{7}\)
\(3+\frac{2}{5}-\frac{3}{4}\times\frac{4}{5}\)
\(=3+\frac{2}{5}-\frac{3}{4}\)
\(=\frac{3\times20+2\times4-3\times5}{20}\)
\(=\frac{60+8-15}{20}\)
\(=\frac{68-15}{20}\)
\(=\frac{53}{20}\)
\(5-\frac{7}{9}+\frac{2}{3}-\frac{5}{6}:\frac{4}{9}\)
\(=5-\frac{7}{9}+\frac{2}{3}-\frac{45}{24}\)
\(=\frac{5\times72-7\times8+2\times24-45\times3}{72}\)
\(=\frac{360-56+48-135}{72}\)
\(=\frac{217}{72}\)
\(\frac{1}{2}+\frac{1}{2}=\frac{1+1}{2}=\frac{2}{2}=1\)
\(\frac{3}{4}+\frac{1}{4}=\frac{3+1}{4}=\frac{4}{4}=1\)
\(\frac{3}{9}+\frac{6}{9}=\frac{3+6}{9}=\frac{9}{9}=1\)
\(1,\frac{3}{5}+\frac{7}{2}-\frac{4}{7}=\frac{42}{70}+\frac{245}{70}-\frac{40}{70}=\frac{247}{70}\)
\(2,\frac{4}{5}-\frac{1}{3}+\frac{3}{4}=\frac{48}{60}-\frac{20}{60}+\frac{45}{60}=\frac{73}{60}\)
\(3,\frac{1}{3}\times\frac{5}{7}:\frac{7}{2}=\frac{5}{21}:\frac{7}{2}=\frac{10}{147}\)
\(4,\frac{1}{2}:\frac{2}{7}\times\frac{4}{7}=\frac{7}{4}\times\frac{4}{7}=1\)
\(5,\frac{19}{15}\times\frac{3}{7}:\frac{4}{9}=\frac{19}{35}:\frac{4}{9}=\frac{171}{140}\)
\(6,\frac{11}{3}:\frac{9}{16}:\frac{3}{8}=\frac{176}{27}:\frac{3}{8}=\frac{1408}{81}\)
_Chúc bạn học tốt _
\(y=\frac{4}{3}-\frac{1}{3072}=\frac{4096}{3072}+\frac{1}{3072}=\frac{4096+1}{3072}=\frac{4097}{3072}\)
\(y=\frac{4}{3}-\frac{1}{3072}=\frac{4096-1}{3072}=\frac{4095}{3072}=\frac{1365}{1024}\)